Self-manage attendance and analysis application using geofencing / Mohd Lukman Hakim Juhari - Juhari, Mohd Lukman Hakim (2019)
The purpose of the project is to overcome the problem regarding the existence attendance system that has many ways to be manipulated by students for their own benefits. We developed this application by using System Development Life Cycle (SDLC) is one the method that guided us to achieve the objectives of the project. We chose to develop the application using android studio software because we only focus for the android user and we also noticed that android platform is the well-known with affordable price for student to own it. The geofencing method had been applied to the application because by using user’s real-time location, it almost impossible to manipulate this application. To should be able for them to clock in their attendance, they need to be in the geofencing area or boundary. We had chosen a group of students from FSKM to test that application. We asked them to be in the boundary but with different pinpoint to test multi-user functionality. We also asked some of them to be near boundary as, this application can notify user that they were nearby the class. As conclusion, this application is practical to apply in environment such as workplace and university because it can take care of user’s integrity.